The link between firm internal resources and the internationalisation of research and development. - Mak, Check Hong. (2008)
In thesis, an exploratory study is carried out to understand the linkages between firm internal resources and the degree of internationalization of R & D and to provide another perspective of looking at the determinants of R & D internationalization arena through the resource-based view.